Early surgical outcomes and influencing factors of high tibial osteotomy - Yan, Zhaolong; Gu, Yange; He, Jiahuan; Zhang, Chenyang; Wang, Jianye; Zhang, Zhenbin; Zhao, Zhang; Li, Shufeng (Frontiers in Surgery, 2023)
Objective:To investigate the influencing factors of functional recovery after high tibial osteotomy(HTO).Methods:A retrospective research was carried on 98 patients who underwent HTO between January 2018 and December 2020. In each case, the medial proximal tibial angle (MPTA), joint line convergence angle (JLCA), femoral tibial angle (FTA), hip-knee-ankle (HKA), weight bearing line (WBL) ratio of the knee joint, opening gap, opening angle, American knee society knee score (KSS),US Hospital for Special Surgery (HSS) score, Lysholm score, and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were measured to determine postoperative function and influential factors of pain through logistic regression analysis.Results: The follow-up time was between 18 and 42 months after operation with an average of 27.66 ± 12.9 per month. Overall functional scores were significantly improved.The influencing factors that may affect the postoperative effect of HTO include age and preoperative WBL ratio of the knee joint. After incorporating these two factors into the multivariate logistic regression analysis, for every 1 unit increase in the preoperative WBL ratio of the knee joint, the probability of postoperative HSS being superior is 1.06 times higher than before. (Exp[β]:1.062,95%CI :1.01-1.1, p = 0.018). For every year increase in age, the probability of an excellent HSS score after surgery was 0.84 times higher than that before surgery (Exp[β]:0.843,95%CI :0.718-0.989, p = 0.036). Preoperative WBL ratio of the knee joint ≥ 14.37 was 17.4 times more likely to be rated as excellent postoperative HSS than that < 14.37 (Exp[β]:17.406,95%CI :1.621-186.927, p = 0.018).Conclusion: The postoperative functional scores of the patients significantly improved.Patients with preoperative WBL ratio of the knee joint≥14.37% had better function after surgery.